FIBROEPITHELIAL POLYP: A RARE PRESENTATION IN SINONASAL CAVITY - Dhanani, Rahim; Danish, Muhammad Hassan; Siddique, Sabeeh; Pasha, Hamdan Ahmed; Siddiq, Muhammad Wasif; Ikram, Mubasher (Journal of Ayub Medical College Abbottabad, 2022)
A fibroepithelial polyp is a benign polypoidal lesion of mesodermal origin. It can present in any area of the body with an epithelial surface. These are relatively more common in skin and genitourinary tract and has been reported very rarely in head and neck region. We report here a rare presentation of fibroepithelial polyp in sinonasal cavity presenting with the symptoms of unilateral nasal obstruction. The patient underwent endoscopic surgical excision and recovered completely. In patients with unilateral sinonasal growing masses fibroepithelial polyp should be considered as one of the possible diagnosis. Sinonasal fibroepithelial polyps have good prognosis after being treated surgically.